Views and experiences on writing certificates for assisted dying: interviews with Swedish physicians - Jonsson, Filip; Sjöstrand, Manne; Kihlbom, Ulrik (Frontiers in Psychiatry, 2025)
IntroThe only legal option for Swedish patients who desire assisted dying (AD) is to travel to Switzerland. To access AD there, patients need medical certificates from their physicians. However, Swedish healthcare law and professional ethical guidelines lack clear directives on how physicians should handle such requests, which may place physicians in perceived ethical and professional dilemmas. How physicians reason about their professional involvement in writing such certificates has previously not been studied in a Swedish context. The aim of this study was to describe and explore physicians’ opinions and reasoning when confronted with requests for AD or requests to enable AD in Switzerland.Material and methods12 semi-structured interviews with physicians from different specialties (oncology, neurology, palliative care, psychiatry, general practice, internal medicine) were conducted, transcribed, and analyzed using thematic analysis.ResultsParticipants felt it was important to address the reasons why patients wanted to pursue AD, including addressing fears, optimizing care, and existential aspects. Participants felt that they should write certificates to enable AD, citing different reasons. Simultaneously, many participants argued that performing AD in Sweden should not be part of their professional role. Some participants were more positively inclined but were still concerned with perceived obstacles.ConclusionParticipants were concerned with the underlying reasons for patients pursuing AD, hoping to address them. Interestingly, although many of the participants expressed skepticism towards AD and its legalization in Sweden, they still supported writing a medical certificate enabling AD in Switzerland.